Pattern of diseases and clinical outcomes in medical intensive care unit at a tertiary hospital in northeastern Tanzania: A three-year retrospective study. - Abid M Sadiq; Kajiru G Kilonzo (PLoS ONE, 2023)
Background The availability of medical intensive care unit (MICU) services is limited, which is the main obstacle to providing optimal care to critically ill patients. Describing disease patterns and clinical outcomes will help make better use of the limited resources. This retrospective study was conducted to determine the pattern and outcome of MICU admissions to aid continuous quality improvement in obstetric care. Materials and methods This was a retrospective study conducted in a tertiary hospital in northeastern Tanzania. Data on participant characteristics were collected from patient records for all MICU admissions to identify the pattern of disease, length of stay, and clinical outcome from 1st January 2018 to 31st December 2020. Descriptive statistics were presented as frequencies, proportions, and tables. The odds ratio was generated for the relationship between MICU admission outcome and participant characteristics. A p-value <0.05 was considered statistically significant. Results Of the 1425 patients analyzed, 780 (54.7%) were males. Most patients (61.5%) were admitted to the MICU from the emergency department. The overall mortality rate was 37.6%. Mortality was associated with being over 75 years old (OR 1.66, 95% CI 1.20-2.30, P 0.002), being transferred from the medical ward (OR 1.46, 95% CI 1.16-1.82, P 0.001), having a communicable disease (OR 2.63, 95% CI 1.98-3.50, P <0.001), and having cardiovascular disease (OR 1.46, 95% CI 1.14-1.86, P 0.002). Conclusion The overall mortality rate in the MICU was high. Elderly patients, transfers from the medical ward, and short ICU stays were significantly associated with the poor outcome of MICU patients. Further studies are needed to better appreciate the causes underlying MICU admission outcomes.